Ljestvica živih bića/Lamarck Osipa Mandel'štama - Benčić, Živa (Array, 1997)
Analyzed is Mandel'štam's poetic interpretation of the evolutionary sheme by Lamarck with man as the perfect form of organic life on its top and primitive, one-celled organisms at its bottom. As opposed to many other modernist and avant-garde poets in the early 20th century such as R. M. Rilke or G. Benn, Mandel'štam perceives the descent from the top of the scale onto lower layers as a negative process resulting in only negative metamorphoses (the loss of sight and hearing, and even the very end of culture). The fact that Mandel'štam in his text Lamarck - like N. Zabolockij in many of his poems written in the same period - renewed Aristotelian evaluative hierarchy of living beings is explained by political situation in the 1930's in Russia. Shadowed by increasing totalitarianism both Mandel'štam and Zabolockij - by means of the scala naturae - paid attention to the non-historical dimension of reality with man as the "crown of creation".